Association between dietary pattern and Helicobacter pylori infection at Queen Elizabeth Hospital, Kota Kinabalu: A case-control study - Vanessa Urie Kasum; Firdaus Hayati; Syed Sharizman Syed Abdul Rahim; Nik Amin Sahid Nik Lah; Tung, Serene En Hui (Elsevier B.V., 2024)
Background Limited studies have reported the association between dietary patterns and Helicobacter pylori (H. pylori) infection in Sabah. Objective The purpose of this study was to assess the association between dietary pattern and H. pylori infection among patients aged 18 years and above that went for first esophagogastroduodenoscopy (OGDS) in 2021 at Queen Elizabeth Hospital (QEH), Kota Kinabalu. Methods Dietary intake of positive H. pylori was compared with healthy subjects by using questionnaire adapted from Malaysian Adult Nutrition Survey (MANS) 2014. Using logistic regression models, we evaluated the association between dietary pattern and H. pylori infection risk. Findings Our finding identified four dietary patterns, namely “high carbohydrate pattern”, “high fiber pattern”, “high fat/cholesterol pattern” and “high salt pattern”. After adjustment for potential confounders, the highest quartile of “high salt pattern” showed greater odds of H. pylori infection (OR = 1.26; 95% Cl: 1.032–1.459; P = 0.045) than lowest quartile, while highest quartile of “high fiber pattern” demonstrated lower odd of the infection (OR = 0.69; 95% Cl: 0.537–0.829; P = 0.008) than those in lowest quartile. If compared with Recommended Nutrient Intake (RNI) 2017, positive H. pylori consumed high carbohydrates and sodium with insufficient fiber intake. Conclusion To conclude, “high fiber pattern” lowers the risk of H. pylori infection while “high salt pattern” increases the infection risk. Our study also highlighted the importance of nutrient intake within daily allowances.